The desire of apartheid - Hook, Derek (Social dynamics, 2023)
This paper has two objectives. It aims, firstly, to provide an overview of the explanatory dilemmas that J.M. Coetzee highlights in his acclaimed essay "The mind of apartheid" in respect of existing theories of apartheid ideology. It then makes recourse, secondly, to a series of concepts in Lacanian psychoanalysis so as to shed light on these dilemmas. Two questions seem to particularly vex Coetzee. Firstly, where should we seek to locate agency in respect of apartheid ideology: predominantly on the side of the subject or predominantly the side of structure? Secondly, if we need to appeal both to subject and structure, then how are we to understand the relation between these two factors in the workings of apartheid ideology? By means of Lacanian conceptualisation, the paper supplements and extends Coetzee's argument according to which the notion of desire is central to understanding the spread and hold of apartheid ideology. The paper then moves on to elaborate a Lacanian understanding of ideological agency which accounts for the relation between subject and structure (or, in Lacanian terms, subject and the symbolic Other) and does so by thinking apartheid as a transaction of desire and/or lack between the two.